Pendampingan Aktivasi Coretax dan Pelaporan SPT Tahunan 2024 - Dian Purnama Sari; Marini Purwanto; S, Patricia Febrina Dwijayanti; Natalia Kristina (Senarai Kearifan Lokal Akuntansi: Jurnal Pengabdian Masyarakat, 2026)
The aim of community service is to provide assistance to people who are still having difficulty reporting their Annual Tax Returns for Individual Taxpayers. This service also provides assistance to taxpayers who want to activate coretax. Even though the Annual Tax Return is reported every year, in reality not all Taxpayers know how to report it correctly. Changes in reporting Annual Tax Returns using Coretax have also become a dynamic in itself among the general public. Coretax activation is also important to carry out in 2025. The implementation method is direct assistance to taxpayers. The results of this community service show that there are still many Taxpayers who need assistance in reporting their Annual Tax Returns. Another finding is the lack of taxpayer knowledge regarding coretax. As a solution to this finding, direct exposure and activation has also been carried out for individual taxpayers.